2001
DOI: 10.1002/1099-0690(200104)2001:8<1459::aid-ejoc1459>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Biosynthetic Precursors of Amarogentin − A Retrobiosynthetic13C NMR Study

Abstract: Keywords: Bioorganic chemistry / Biosynthesis / Isotopic labeling / NMR spectroscopy / Enzyme catalysis A root culture of Swertia chirata (Gentianaceae) produced the natural bitter compound amarogentin in 0.1% (dry weight) yield. The biosynthesis of amarogentin was studied by in vivo experiments, using [1-13 C]glucose, [U-13 C 6 ]glucose, [1-13 C]acetate, [2-13 C]acetate, [7-13 C]benzoic acid, [ring-13 C 6 ]cinnamic acid, or [7-13 C]shikimic acid as precursors. Comparison between labeling patterns of amarogent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 27 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…The non-mevalonate pathway is operative during the biosynthesis of the bitter flavour additive amarogentin 86. 49 This compound is produced in roots of the plant Swertia chirata (green gentian) and is used as a flavouring for enzian schnapps. Feeding studies with labelled precursors showed that the biphenyl moiety was probably biosynthesised from a PKS pathway using a shikimate derived 3-hydroxybenzoyl CoA starter unit.…”
Section: Pks From Plants and Algaementioning
confidence: 99%
“…The non-mevalonate pathway is operative during the biosynthesis of the bitter flavour additive amarogentin 86. 49 This compound is produced in roots of the plant Swertia chirata (green gentian) and is used as a flavouring for enzian schnapps. Feeding studies with labelled precursors showed that the biphenyl moiety was probably biosynthesised from a PKS pathway using a shikimate derived 3-hydroxybenzoyl CoA starter unit.…”
Section: Pks From Plants and Algaementioning
confidence: 99%
“…A brevetoxina B biossintetizada a partir de acetato [1,[2][3][4][5][6][7][8][9][10][11][12][13] Mais recentemente, estas técnicas de marcação foram empregadas na elucidação das rotas de vários outros metabólitos policetídicos complexos de dinoflagelados 15 .…”
Section: (Esquema 12)unclassified
“…Plant benzoic acids arise from either shikimate pathway intermediates or the phenylpropanoid pathway. Examples of shikimate‐derived benzoates are 3‐hydroxybenzoic acid in Centaurium erythraea and Swertia chirata , salicylic acid in Arabidopsis thaliana and Nicotiana benthamiana , gallic acid in Rhus typhina and 2,3‐dihydroxybenzoic acid in Catharanthus roseus (Ishikura et al ., ; Moreno et al ., ; Werner et al ., ; Wang et al ., ; Catinot et al ., ). Many plants synthesise isochorismate, which serves as the intermediate for the biosynthesis of O ‐succinylbenzoic acid, salicylic acid and 2,3‐dihydroxybenzoic acid (Mustafa et al ., ; Bartsch et al ., ).…”
Section: Introductionmentioning
confidence: 98%